Enabling methanol oxidation by an interacting hybrid nanosystem of spinel Co3O4 nanoparticle decorated MXenes. Issue 11 (22nd February 2022) - Baruah, Kashmiri; Deb, Pritam
Abstract : Abundant redox sites at surfaces and interfaces, Lewis acid–base interactions between Co3 O4 nanoparticles and –OH hydrophilic terminations of MXene nanosheets lead to efficient methanol oxidation of the catalysts developed. Abstract : For the successful implementation of direct methanol fuel cells in commercial applications, highly efficient and durable non-noble electrocatalysts based on conducting and stable non-carbonaceous supports can be potential candidates. Herein, spinel Co3 O4 nanoparticles are decorated over Ti3 C2 MXene nanosheets for methanol oxidation. The hybrid nanosystem Ti3 C2 /Co3 O4 (TC) reduces restacking of MXene nanosheets, which offers a larger surface area for Co3 O4 dispersion, leading to a shorter path for the charge carriers. TC coated on glassy carbon (GC) exhibits a MOR current density of 38.38 A g −1 which is 2.9 times higher than that of Co3 O4 /GC in 1.5 M methanol at a 20 mV s −1 scan rate. The hydrophilic terminations on the surface of MXenes create strong interactions with the Co3 O4 nanoparticles, which increase the MOR kinetics of the nanocomposite. A low onset potential (0.32 V), high oxidation current density of the nanocomposite, efficient durability and cycling stability up to 200 CV cycles make this nanocomposite a better alternative to the state-of-the-art noble-metal electrocatalysts.